2016
DOI: 10.1109/jphot.2016.2577594
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Poly-Silicon-Layer-Based Spot-Size Converter for Efficient Coupling Between Silicon Waveguide and Standard Single-Mode Fiber

Abstract: A novel spot-size converter (SSC) incorporating phase matched polycrystalline-silicon (Poly-Si) multi-layer is proposed and optimised for efficient nanophotonic coupling, which can be fabricated by using the CMOS compatible process and can be directly integrated. An efficient algorithm, combining the rigorous H-field based full-vectorial finite element method and the least squares boundary residual method, is developed for the design optimization of the SSC. Use of simple single layer and multi-layer Poly-Si b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In the previous design of Jiang et al (2016), an 11 layer based SSC with h = 105 nm, s = 400 nm, and s = 200 nm was studied. Although the Poly Si layers were single moded vertically but it should be noted that they can support higher order modes laterally.…”
Section: Previous Designmentioning
confidence: 99%
See 4 more Smart Citations
“…In the previous design of Jiang et al (2016), an 11 layer based SSC with h = 105 nm, s = 400 nm, and s = 200 nm was studied. Although the Poly Si layers were single moded vertically but it should be noted that they can support higher order modes laterally.…”
Section: Previous Designmentioning
confidence: 99%
“…A spot size converter (SSC) based on a different design concept (Jiang et al 2016) has been recently reported. This SSC comprises of two evanescently coupled waveguides: a standard nanowire and a phase matched array of Polycrystalline Silicon waveguides.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations